Hyers-Ulam Stability and Existence Criteria for the Solution of Second-Order Fuzzy Differential Equations - Noor Jamal; Muhammad Sarwar; M. Motawi Khashan (Journal of Function Spaces)
In this paper, existence, uniqueness, and Hyers-Ulam stability for the solution of second-order fuzzy differential equations (FDEs) are studied. To deal a physical model, it is required to insure whether unique solution of the model exists. The natural transform has the speciality to converge to both Laplace and Sumudu transforms only by changing the variables. Therefore, this method plays the rule of checker on the Laplace and Sumudu transforms. We use natural transform to obtain the solution of the proposed FDEs. As applications of the established results, some nontrivial examples are provided to show the authenticity of the presented work.